2019
DOI: 10.3390/ijms20215476
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Organized Porcine Testicular Organoids in Solubilized Hydrogels from Decellularized Extracellular Matrix

Abstract: Cryopreservation of immature testicular tissue (ITT) prior to chemo/radiotherapy is now ethically accepted and is currently the only way to preserve fertility of prepubertal boys about to undergo cancer therapies. So far, three-dimensional culture of testicular cells isolated from prepubertal human testicular tissue was neither efficient nor reproducible to obtain mature spermatozoa, and ITT transplantation is not a safe option when there is a risk of cancer cell contamination of the testis. Hence, generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 77 publications
1
54
0
Order By: Relevance
“…Two studies reported the production of porcine testicular “organoids” from dissociated testis [ 44 , 45 ]. The developed testicular structures contained all relevant cell types in a 3D organization with physiological cell–cell interactions of germ cells with supporting cells [ 44 ].…”
Section: Research In Major Livestock and Companion Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported the production of porcine testicular “organoids” from dissociated testis [ 44 , 45 ]. The developed testicular structures contained all relevant cell types in a 3D organization with physiological cell–cell interactions of germ cells with supporting cells [ 44 ].…”
Section: Research In Major Livestock and Companion Animalsmentioning
confidence: 99%
“…In addition, the cultured testicular structures contained Sertoli cells and germ cells which assembled into seminiferous tubule-like structures delimited by a basement membrane along with Leydig cells and peritubular cells. In one of these studies, the cellular structures were maintained for 45 days [ 45 ]. However, long term self-renewal was not well-controlled, as the number of Sertoli cells increased and that of Leydig cells decreased over time.…”
Section: Research In Major Livestock and Companion Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 116,119 ] Nonetheless, dECM‐based hydrogels are still relatively underexplored for developing in vitro tumor models. [ 120–122 ]…”
Section: Hydrogels and The Tumor Microenvironment Ecmmentioning
confidence: 99%
“…Porcine testicular organoids obtained from testicular single cells [ 130 ] embedded in tissue‐specific dECM gels underwent seminiferous tubule organization comparable to the native organ. [ 131 ] The culture of freshly isolated, pre‐aggregated testicular cells in the very soft decellularized testicular dECM gel (storage modulus below 20 Pa) was clearly superior to the reference culture in collagen hydrogels (storage modulus 75–100 Pa). The dECM gel‐grown testicular organoids were maintained for 45 days in culture and secreted stem cell factor and testosterone demonstrating functionality.…”
Section: Engineering Cell‐ and Tissue‐instructive Hydrogel Materialsmentioning
confidence: 99%